2020
DOI: 10.1007/s40843-020-1307-x
|View full text |Cite
|
Sign up to set email alerts
|

Anti-photocorrosive photoanode with RGO/PdS as hole extraction layer

Abstract: Photoelectrochemical (PEC) hydrogen production is of great interest as an ideal avenue towards clean and renewable energy. However, the instability and low energy conversion efficiency of photoanodes hinder their practical applications. Here we address these issues by introducing a hole extraction layer (HEL) which could rapidly transfer and consume photogenerated holes. The HEL is constructed by reduced graphene oxide (RGO) and other cocatalysts that enable rapid transfer and subsequent consumption of holes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 40 publications
(36 reference statements)
0
16
0
Order By: Relevance
“…The existence of elemental tellurium causes the XRD diffraction peak of CdSe to shift to lower 2θ values. 17,37 High-resolution transmission electron microscopy (HRTEM) images of CST and CST@CS NWs showed lattice spacings of 0.369 and 0.355 nm, which we attributed to the (100) plane of wurtzite-phase CdSe and the (100) plane of wurtzite-phase CdS, respectively (see Figures S7a and S8a in the Supporting Information). Besides, the energy dispersion spectra (EDS) and EDS elemental mapping images of CST nanowires and CST@CS core-shell nanostructures revealed that both elemental cadmium and selenium are uniformly distributed in the CST NWs, while the elemental tellurium is concentrated in the core of the CST NWs, and elemental sulfur is present only in the CdS shell (see Figures S7b−d, S8b, S8c, and S9a in the Supporting Information).…”
Section: T H Imentioning
confidence: 95%
See 3 more Smart Citations
“…The existence of elemental tellurium causes the XRD diffraction peak of CdSe to shift to lower 2θ values. 17,37 High-resolution transmission electron microscopy (HRTEM) images of CST and CST@CS NWs showed lattice spacings of 0.369 and 0.355 nm, which we attributed to the (100) plane of wurtzite-phase CdSe and the (100) plane of wurtzite-phase CdS, respectively (see Figures S7a and S8a in the Supporting Information). Besides, the energy dispersion spectra (EDS) and EDS elemental mapping images of CST nanowires and CST@CS core-shell nanostructures revealed that both elemental cadmium and selenium are uniformly distributed in the CST NWs, while the elemental tellurium is concentrated in the core of the CST NWs, and elemental sulfur is present only in the CdS shell (see Figures S7b−d, S8b, S8c, and S9a in the Supporting Information).…”
Section: T H Imentioning
confidence: 95%
“…The optical band gaps of CST, CSST-0.5, CSST-1.0, and CSST-2.0 are 1.51, 2.06, 2.26, and 2.39 eV, respectively. Compared with individual CST NWs, the introduction of elemental sulfur enlarges the We then calculated the work function Φ, 17,38 which is defined as the relative energy between the vacuum level and the Fermi level:…”
Section: T H Imentioning
confidence: 99%
See 2 more Smart Citations
“…Attempts have been made to deposit different photocatalytic components on the ''host'' to build various interfacial heterojunctions including type I heterojunctions, Schottkey junctions, and Ohmic junctions. These can promote photo-induced charge separation and transportation [17][18][19][20]. Some excellent nanostructures can be found in the literature with considerable improvement for PEC performance, such as CdS nanorod@SnO 2 nanobowl [21], Fe 2 O 3 nanorod@nanobowl [22], 3D g-C 3 N 4 /Ni(OH) 2 [23], WO 3 / BiVO 4 /Co-Pi inverse opal [24], and fluorine-doped tin oxide (FTO)/FTO-nanocrystal/TiO 2 inverse opal [25].…”
Section: Introductionmentioning
confidence: 99%